2004
DOI: 10.1099/vir.0.19479-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of onco/lentivirus hybrids results in formation of infectious but not of replication-competent viruses

Abstract: To achieve specific gene transfer into human CD4 + cells, murine leukaemia virus (MLV)-based pseudotype vector particles were generated employing Env variants derived from human or simian immunodeficiency virus (HIV-1 or SIVagm). Here, we describe the generation of full-length onco/lentivirus hybrid genomes comprising components of MLV and HIV-1 or SIVagm, respectively, to assess the possibility of replication-competent hybrid virus formation. The env reading frame of an infectious molecular clone of MLV was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This infectivity is clearly lower than that usually observed for retroviral particles, where 1 in 100 to 1,000 particles is infective (46). Nevertheless, infectivity is clearly codetermined by the glycoproteins used for pseudotyping retroviral vector particles (48,49) and may vary by at least two logs (49). Accordingly, glycoproteinspecific differences have been observed also in this study when VSV-G or MV-H/F expression plasmids were titrated against the other constituents of PTVs during establishment of PTV generation (Fig.…”
Section: Generation and Characterization Of Lentiviral Protein Transfmentioning
confidence: 71%
“…This infectivity is clearly lower than that usually observed for retroviral particles, where 1 in 100 to 1,000 particles is infective (46). Nevertheless, infectivity is clearly codetermined by the glycoproteins used for pseudotyping retroviral vector particles (48,49) and may vary by at least two logs (49). Accordingly, glycoproteinspecific differences have been observed also in this study when VSV-G or MV-H/F expression plasmids were titrated against the other constituents of PTVs during establishment of PTV generation (Fig.…”
Section: Generation and Characterization Of Lentiviral Protein Transfmentioning
confidence: 71%
“…J02255) and an additional Sfi I-site at position 5389 removed by mutation. The start codon of MLV env (position 5777) was deleted to allow translation to start at the inserted GFP sequence [16]. We replaced GFP with RFP, which was introduced as a Sfi I-Cla I fragment.…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear what determines the incidence of intracellular versus cell surface assembly. Indeed, numerous EM analyses performed with transfected MLV Gag or reconstituted viruses, usually in human (293T), monkey (Cos), or hamster (BHK21) cell lines, described exclusive budding at the plasma membrane [ 26 - 28 ]. At the opposite, only two studies (ours and [ 23 ]) showed the coexistence of intracellular and cell surface in chronically infected cells.…”
Section: Discussionmentioning
confidence: 99%